2017
DOI: 10.18632/oncotarget.21336
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PP2A activates AMPK signaling to inhibit colorectal cancer cells

Abstract: LB-100 is a novel PP2A inhibitor. Its activity in human colorectal cancer (CRC) cells was tested. The in vitro studies demonstrated that LB-100 inhibited survival and proliferation of both established CRC cells (HCT-116 and HT-29 lines) and primary human colon cancer cells. Further, LB-100 activated apoptosis and induced G1-S cell cycle arrest in CRC cells. LB-100 inhibited PP2A activity and activated AMPK signaling in CRC cells. AMPKα1 dominant negative mutation, shRNA-mediated knockdown or complete knockout … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 72 publications
0
15
1
Order By: Relevance
“…As cAMP negatively regulates PKA-reg this further supports the downregulation of this gene. Protein phosphatase 2 ( PP2A ) expression was also increased, which can lead to increased cell survival in RCC through 5-hydrotryptamine receptor 1A signaling and may have possible actions on the androgen receptor (Dai et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…As cAMP negatively regulates PKA-reg this further supports the downregulation of this gene. Protein phosphatase 2 ( PP2A ) expression was also increased, which can lead to increased cell survival in RCC through 5-hydrotryptamine receptor 1A signaling and may have possible actions on the androgen receptor (Dai et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It is well-documented that AMPK signaling has anti-proliferative role. Dai and her colleagues have reported that activated AMPK signaling inhibits survival and proliferation and activates apoptosis in colorectal cancer cells 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Cells were harvested every 5 min during the first hour of treatment with either 5 M SH-BC-893 (heavy label) or 50 M C2-ceramide (medium label) or 10 M LB-100 (medium label) or DMSO (light label). Drug concentrations used for treatments are based on previously published references (5,7,19). Cells were collected by pipetting 75 ml (25 ml per SILAC channel) of culture into 425 ml of Ϫ80°C precooled ethanol.…”
Section: Methodsmentioning
confidence: 99%